Analisis Visual terhadap Pemilihan Jenis Vegetasi sebagai Border antara Jalur Pedestrian dan Jalur Kendaraan - Dibyanti Danniswari; Permata, Nike Dyah; Sari, Pawitra; Prastiyo, Yulius Budi; Nabila, Rizka (JURNAL RUANG / ISSN : 2085-6962, 2025)
The selection of border elements between pedestrian walkways and vehicular roads is a critical aspect of urban landscape design that supports safety, comfort, and visual aesthetics. One widely adopted approach is the use of vegetation as a natural separator. This study aims to visually analyze the effectiveness of plant selection in separating these two functional zones, focusing on safety, visual legibility, and aesthetic value. This research seeks to strengthen through landscape enhancement while providing a pleasant pedestrian experience. The study employed one original site photograph and four digitally altered (montaged) images, which were evaluated by 30 respondents using structured questionnaires. Scenic Beauty Estimation (SBE) and Semantic Differential (SD) methods were applied to assess visual aesthetic quality. The results indicate that plant type significantly influences perceived aesthetic quality and is closely associated with user perception. The study concludes that medium-height shrubs are the most suitable choice for pedestrian borders, as they enhance visual aesthetics while maintaining a functional and environmentally responsive road landscape.